FGF-23 Levels before and after Renal Transplantation. (17th May 2009) - Economidou, Domniki; Dovas, Spyros; Papagianni, Aikaterini; Pateinakis, Panagiotis; Memmos, Dimitrios
Abstract : Phosphatonin fibroblast growth factor-23 (FGF-23) is involved in phosphate (P) excretion and vitamin D metabolism. Recently, FGF-23 has been suggested to be responsible for the hypophosphatemia and inappropriately low calcitriol levels observed after renal transplantation. We performed a prospective study to investigate FGF-23 levels in patients with end-stage renal disease before and after renal transplantation and their probable association with markers of bone and mineral metabolism. Intact FGF-23 levels were determined before and at 3, 6, and 12 months posttransplantation in 18 renal transplant recipients. Intact parathyroid hormone (iPTH), calcium (Ca), P, 25(OH)VitD, and 1, 25(OH) 2 VitD levels were measured at the same time periods. Renal threshold phosphate concentration (TmPO 4 /GFR) was also calculated at 3, 6, and 12 months posttransplantation. The results showed that FGF-23 levels decreased by 89% 3 months posttransplantation (346± 146 versus 37± 9 pg/mL, P < .01 ) and remained stable throughout the study period. iPTH and P levels also decreased significantly after renal transplantation, while Ca and 1, 25(OH) 2 VitD increased. Pretransplantation FGF-23 was significantly correlated with P levels at 3 months posttransplantation (P < .005 ). In conclusion, FGF-23 levels decrease dramatically after successful renal transplantation. Pre-transplantation FGF-23 correlate with P levels 3 months posttransplantation.